Análisis sobre el manejo y manipulación de la carga peligrosa nitrato de amonio en la sociedad portuaria de Santa Marta del 2021 al 2022 (2023)
The structure of this grade written assignment is organized in the following way: first, we present a theoretical mark, which abort important aspects related to the ammonium nitrate. Aspects, like its characteristics and risks, its regulations and applications, the technology and its manipulation techniques, proper storage, its logistic and right way of transporting. This assignment describes the methodology used to the research and investigation, including the approaching, type of researching method, companies involved, samples, data collect and the methodology used to it. The following research will be focused in the test and the hazardous ammonium nitrate cargo handling by Santa Marta’s’ port society, comparing with the established by the regulations in force, to the manipulation of this type of cargo, due the complexity in the logistic processes of this material it is of great relevance, the research and data processing of its information to the city of Santa Marta and for the proper company in study.